Effect of Low Moisture Level on Catalase Activity in Some Crop Plants During Juvenile Phase - Vora, A B; Patel, H C; Vyas, A V; Patel, B R; Patel, J A (Annals of Arid Zone, 2016)
Seeds of maize Cv. Ganga 5, gram cv. Chafa and Sesamum Cv. Patan 64 were germinated under "adequate" and "low" moisture levels. Catalase activity was determined in the growing axis and in endosperm of maize and cotyledons of gram as well as in the seedings of Sesamum at 24 hourly intervals for 96 hours. LOW moisture level considerably depressed the catalase activity in growing axis of maize and gram seedlings and cotyledon of gram. There was no effect of low moisture on the enzymic activity of endosperm of maize. 10 8e8amum seedlings, low moisture level increased the enzymic activity at 24 and 72 hours of germinations and 72 hours of germinations and decreased considerably at 48 hours of germination.